An analysis of misoprostol effectiveness in second trimester pregnancy terminations: Misoprostol and pregnancy terminations - Ak, Mehmet; Dolanbay, Mehmet; Kütük, Mehmet Serdar (Journal of Surgery and Medicine, 2023)
Background/Aim: Misoprostol is frequently used as a single agent in pregnancy terminations. However, it increases the risk of uterine rupture in patients who have had previous uterine surgery and terminations due to stillbirths. Therefore, it is used with concern by clinicians. The aim of this study was to evaluate the clinical features of the groups that responded and did not respond to termination treatment with misoprostol in a tertiary center and to investigate its efficacy and safety. Methods: The study design was comprised of a retrospective cohort study. A total of 114 second trimester pregnancies (between 13-24 weeks gestational age) were included in the study. These pregnancies were indicated for termination based on the prenatal diagnosis unit for fetal or maternal causes. According to the International Federation of Gynecology and Obstetrics (FIGO) directions, misoprostol was applied in the following dosages: for 13-17 weeks gestational ages, one tablet per 6 hours; for 18-26 gestational ages, ½ tablet per 6 hours; and for other indications 2 tablets per 3 hours were administered. If the patient had had a previous cesarean operation, all doses were halved. After the first 24 hours, the percentage and demographics results, such as age, body mass index (BMI), gravida, number of cesareans, number of curettages, cervical lengths, BISHOP scores, gestational age, amniotic fluid index, and fetal cardiac beat of the patients with miscarriage, were recorded. Results: The number of cases resulting in miscarriage within 24 hours were 84 (73.7%) and within 48 hours were 14 (12.2%). The total of misoprostol doses used were 8 tablets of 200 mg, mean time until the complete abortion was 17 hours. Sixteen patients required additional treatment, of whom four required Foley catheterization, five required D&E, seven required resting, and no one required a hysterectomy. Uterine rupture occurred in two patients who needed laparotomic surgery. The maternal age (P=0.340), BMI (P=0.790), gravida (P=0.270), previous cesarean history (P=0.390), previous curettage number (P=0.520), cervical length (P=0.380), Bishop score (P=0.190), gestational age (P=0.072), amniotic fluid index (P=0.470) and presence of fetal cardiac beat (P=0.350) were similar between groups Conclusion: Our results indicated that misoprostol is a safe, useful, and effective treatment option for second trimester medical terminations. Caution should be exercised in its use in patients with a history of uterine surgery.